Pengaruh Pembelajaran E-Learning Model Web Centric Course Terhadap Pemahaman Konsep dan Kemandirian Belajar Matematika Siswa - Arifin, Fatkhul; Herman, Tatang (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2018)
The aim of the study is to analyze the conceptual understanding and self regulated learning in mathematics between students who got the e-learning model web centric course and learning with the power point, and to find out the appropriate e-learning design in learning math for elementary school. The subject of this study is all of the 5th grade students of Islamic Elementary School (MI) private in Jakarta, while the sample is two classes of the population. The instruments used in this study are essay, questionnaire, and observation sheet. The results showed that 1) the conceptual understanding of mathematics students who get e-learning model web centric course better than students who get the learning using power point, 2) self regulated learning of students who get e-learning model web centric course better than students who get the learning using power point, 3) e- learning design that fits in the learning of mathematics in primary schools is an e-learning design, incorporating text, images and animations as well as providing convenience for group discussion. Based on these results it can be concluded that the e-learning web-centric model of course affect the conceptual understanding of mathematics and self regulated learning elementary school students.